Development and validation of malaria knowledge questionnaire and the level of malaria knowledge among population in Kuala Krai and Gua Musang, Kelantan - Ismail, Mohd Hafiz Che (2024)
Malaysia has made significant progress in reducing malaria cases, achieving zero local transmission in 2018. However, imported cases continue to pose risks of reintroduction. Assessing local knowledge is vital for targeted education as it empowers communities with the information necessary to take appropriate actions to prevent malaria transmission, thereby reducing the risk of transmission and contributing to the overall goal of malaria elimination.